2006
DOI: 10.1213/01.ane.0000198332.51475.50
|View full text |Cite
|
Sign up to set email alerts
|

Giving Toys to Children Reduces Their Anxiety About Receiving Premedication for Surgery

Abstract: Children have increased anxiety during the preoperative period. The administration of oral premedication to children is often met with apprehension, reluctance, or refusal. We sought to determine whether giving a small toy to the children would decrease the anxiety associated with taking oral premedication. This was a prospective study involving 100 children 3-6 yr of age randomized into two equal groups. The anxiety of each child was assessed using the Modified Yale Preoperative Anxiety Scale. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 7 publications
0
39
0
8
Order By: Relevance
“…A wide variety of approaches have been proposed to minimize the potential negative effects of surgery and hospitalization, in particular the use of toys and other entertainment materials [12,[79][80][81], including music [82,83], humor [84], magic [85], hospital clowns [20,86], guided visits to the hospital and operating room [87] and educational preoperative programs [11,66,73,88]. The literature also recommends that preoperative instruments should be brief, portable, inexpensive, and easy to administer [89].…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of approaches have been proposed to minimize the potential negative effects of surgery and hospitalization, in particular the use of toys and other entertainment materials [12,[79][80][81], including music [82,83], humor [84], magic [85], hospital clowns [20,86], guided visits to the hospital and operating room [87] and educational preoperative programs [11,66,73,88]. The literature also recommends that preoperative instruments should be brief, portable, inexpensive, and easy to administer [89].…”
Section: Discussionmentioning
confidence: 99%
“…3,8,10,14,18 The first models of specific programs for children that would undergo surgery in the hospital were developed in the 1970s. 4 In these models, children were offered an overview of the anesthesia and surgery by means of videos or puppet theater.…”
Section: Discussionmentioning
confidence: 99%
“…After the present research project was approved by This instrument is validated to measure the anxiety of children during the preoperative period and it has been used in several studies to measure the level of preoperative anxiety and its relation with interventions using toys, 3 videogames, 8 presence of clowns, 10 playing doctor, and movies. 4 However, we could not find any Brazilian studies with the same objective as the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Golden, Pagala [53] found that giving a toy before the anaesthesia induction is an easy, safe and economical way of reducing CPA and may reduce the dose of midazolam necessary to decrease anxiety. Similar results were reported by Patel, Schieble [54] who investigated the use of an hand-held videogame in the holding area and by Lee, Lee [55] who reported that children who watched animated cartoons in the waiting areas had significantly lower anxiety scores than those in the control group.…”
Section: Distractive Techniquesmentioning
confidence: 99%